Variation law of adsorption heat of methane and coal with inhomogeneous potential well - Zeng-Chao Feng; Chen Wang; Dong Zhou; Dong Zhao (Adsorption Science & Technology)
The non-uniform structures of coal deposits make potential well distribution on the coal surface inhomogeneous. Deep potential wells adsorb methane molecules more easily than shallow potential wells. The methane adsorption heat release differs according to the depths of the potential wells. During isobaric adsorption, the adsorption heat in the high-temperature stage is significantly higher than that in the low-temperature stage. A lower adsorption pressure results in greater adsorption heat variation during a temperature increase. During the isothermal adsorption process, the adsorption heat is higher in the low-pressure stage, with the preferential adsorption characteristics of deep potential wells.